1, 4‐Dihydropyridine derivatives without Ca2+‐antagonist activity up‐regulate Psma6 mRNA expression in kidneys of intact and diabetic rats. (4th December 2015) - Ošiņa, Kristīne; Rostoka, Evita; Sokolovska, Jelizaveta; Paramonova, Natalia; Bisenieks, Egils; Duburs, Gunars; Sjakste, Nikolajs; Sjakste, Tatjana
Abstract : Impaired degradation of proteins by the ubiquitin–proteasome system (UPS) is observed in numerous pathologies including diabetes mellitus (DM) and its complications. Dysregulation of proteasomal degradation might be because of altered expression of genes and proteins involved in the UPS. The search for novel compounds able to normalize expression of the UPS appears to be a topical problem. A novel group of 1, 4‐dihydropyridine (1, 4‐DHP) derivatives lacking Ca2+‐antagonists activities, but capable to produce antidiabetic, antioxidant and DNA repair enhancing effects, were tested for ability to modify Psma6 mRNA expression levels in rat kidneys and blood in healthy animals and in rats with streptozotocin (STZ) induced DM. Psma6 gene was chosen for the study, as polymorphisms of its human analogue are associated with DM and cardiovascular diseases. 1, 4‐DHP derivatives (metcarbatone, etcarbatone, glutapyrone, J‐9‐125 and AV‐153‐Na) were administered per os for three days (0.05 mg/kg and/or 0.5 mg/kg). Psma6 gene expression levels were evaluated by quantitative PCR. Psma6 expression was higher in kidneys compared to blood. Induction of diabetes caused increase of Psma6 expression in kidneys, although it was not changed in blood. Several 1, 4‐DHP derivatives increased expression of the gene both in kidneys and blood of control and model animals, but greater impact was observed in kidneys. The observed effect might reflect coupling of antioxidant and proteolysis‐promoting activities of the compounds. Copyright © 2015 John Wiley & Sons, Ltd.